A survey of entodiniomorphid ciliates in chimpanzees and bonobos - Pomajbíková, Kateřina; Petrželková, Klára J; Profousová, Ilona; Petrášová, Jana; Kišidayová, Svetlana; Varádyová, Zora; Modrý, David (American journal of physical anthropology, 2010)
Intestinal entodiniomorphid ciliates are commonly diagnosed in the feces of wild apes of the genera Pan and Gorilla. Although some authors previously considered entodiniomorphid ciliates as possible pathogens, a symbiotic function within the intestinal ecosystem and their participation in fiber fermentation has been proposed. Previous studies have suggested that these ciliates gradually disappear under captive conditions. We studied entodiniomorphid ciliates in 23 captive groups of chimpanzees, three groups of captive bonobos and six populations of wild chimpanzees. Fecal samples were examined using Sheather's flotation and Merthiolate-Iodine-Formaldehyde Concentration (MIFC) methods. We quantified the number of ciliates per gram of feces. The MIFC method was more sensitive for ciliate detection than the flotation method. Ciliates of genus Troglodytella were detected in 13 groups of captive chimpanzees, two groups of bonobos and in all wild chimpanzee populations studied. The absence of entodiniomorphids in some captive groups might be because of the extensive administration of chemotherapeutics in the past or a side-effect of the causative or prophylactic administration of antiparasitic or antibiotic drugs. The infection intensities of ciliates in captive chimpanzees were higher than in wild ones. We suppose that the over-supply of starch, typical in captive primate diets, might induce an increase in the number of ciliates. In vitro studies on metabolism and biochemical activities of entodiniomorphids are needed to clarify their role in ape digestion.
Keywords: Animals; Gorilla gorilla; infekce prvoky kmene Ciliophora; feces; Feces; Uganda; divoká zvířata; Symbiosis; Ciliophora; stromy; Pan paniscus; Animals, Wild; Pan troglodytes; nemoci lidoopů; ekosystém; Ape Diseases; zvířata v ZOO; Ciliophora Infections; Ecosystem; symbióza; zvířata; Trees; Animals, Zoo